Development of a Hybrid Bioethanol–Seawater Electrolyte from Oil Palm Empty Fruit Bunch Waste for Sustainable Bio-Battery Applications - Dwi Syafitri; Muhammad Yerizam; Rusdianasari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The increasing demand for renewable energy necessitates innovative solutions utilizing abundant agricultural waste. This study investigates the development of a novel hybrid liquid electrolyte that combines crude bioethanol derived from oil palm empty fruit bunches (OPEFB) with natural seawater for sustainable bio-battery systems. The main novelty lies in leveraging the synergistic effect between the stable, polar organic medium of OPEFB bioethanol and the high conductivity of seawater (49.87 mS/cm), thereby eliminating reliance on synthetic chemicals. The OPEFB underwent delignification (6% NaOH) and hydrolysis prior to fermentation. Gas Chromatography-Mass Spectrometry (GC-MS) confirmed the successful bioconversion into crude bioethanol (39.84% relative peak area). Electrochemical evaluations using a Zn/Cu electrode configuration revealed that the delignification-based solution at an optimal 70:30 (bioethanol-to-seawater) mixture ratio generated a maximum power output of 0.84 mW. Significantly, this research provides a dual-solution approach: valorizing massive lignocellulosic waste while advancing eco-friendly energy storage. Practically, the formulated hybrid bio-battery is highly viable for ultra-low-power applications, demonstrably capable of continuously powering small Light Emitting Diodes (LEDs) for up to 24 hours and mini DC fans for 9 hours. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 9: Industry, Innovation, and InfrastructureSDG 12: Sustainable consumption and productionSDG 13: Climate Action